ANALISIS PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA APLIKASI KOMUNIKASI SNAAPP PADA SD IGNATIUS SLAMET RIYADI KARAWANG - Akbar, Niko Faizal (Universitas Mercu Buana, 2019)
AbstractThis study aims to find out about: 1) the effect of perceived usefulness on user satisfaction, 2) the effect of perceived ease of use on user satisfaction, 3) the effect of service quality on user satisfaction, 4) the effect of perceived ease of use on perceived usefulness, 5) the effect of perceived usefulness and perceived ease of use on user satisfaction simultaneously. This type of quantitative research with a population of Ignatius Slamet Riyadi Karawang Elementary School parents user as many as 300 people, using techniques Quota Sampling and using the Slovin formula as a sample determination, found a sample of 171 people. Analysis of data with multiple linear regression results: 1) perceived usefulness has a positive and significant affects on user satisfaction, 2) perceived ease of use has a positive and significant effect on user satisfaction, 3) service quality has a positive and significant effect on user satisfaction, 4) perceive ease of use has a positive and significant effect on perceived usefulness, 5) perceived usefulness and perceived ease of use have a positive and significant effect on user satisfaction simultaneously.